(untitled) (Journal of Hama University, 2024)
This study aims to analyze and measure the relationship between exchange rate fluctuations and re-evaluation of the structural position of the private commercial banks listed on the Damascus Stock Exchange. The number is (11) banks for the time series ((2011-2021) using the statistical program (EVIEWS10). The results of the study showed that there was a direct and statistically significant relationship between the profits of the revaluation of the structural cutting position and the official exchange rate, and the results of the Granger causal test showed that there is a two-way causal relationship between the profits of the revaluation of the structural cutting position and the official exchange rate, in addition to the existence of a positive effect of the exchange rate The official profit of the re-evaluation of the structural cutting position in the short term appears after two quarters, so that this effect turns into a negative effect starting from the third slowdown period, and this negative effect continues in the long term, and that the value of the error correction coefficient for the estimated model indicates a lack of efficiency in private commercial banks. In managing exchange rate risks, as it takes a year to return to the equilibrium.